Cystic appearance - a new feature of solid fibrous tumours in the lacrimal gland: a case report with literature review - Ancuta-Augustina Gheor; Dana Cristina Terzea; Iulia Burcea; Roxana Dusceac; Cristina Capatina; Catalina Poiana (BMC, 2019)
Abstract Background Solitary fibrous tumours (SFTs) rarely occur in the orbit, especially in the lacrimal area. These tumours are mostly solid. Cystic changes have been documented, but they remain very rare. Only three cases of primary orbital solitary fibrous tumours with cystic changes have been reported in the literature, but no cases have been reported to occur in the lacrimal gland. Solitary fibrous tumours generally follow a benign course and are treated definitively with surgical excision. Data from the literature suggest that the cystic nature of SFT presents a risk of recurrence and could be a harbinger of malignancy. Case presentation A 42-year-old woman was admitted to the endocrinology department for right unilateral exophthalmia and epiphora in the last 8 months. An ophthalmological evaluation showed exophthalmia only in the right eye (22 mm) and normal visual acuity, visual field and extraocular movements. Investigations revealed normal thyroid function. Orbital magnetic resonance imaging detected a 4 × 2,2 × 2,7 cm septate pseudocystic mass in the right lacrimal gland. Given her lacrimal gland tumour diagnosis, the patient was submitted for neurosurgical intervention with total ablation of the tumoural mass and complete right dacryoadenectomy. Although the intraoperative extemporaneous examination results were suggestive of a haemangiopericytoma, histological and immunocytochemical examination showed an extrapleural SFT. The postoperative clinical evolution was favourable, with remission of the exophthalmia. Fifteen months after surgery, no signs of recurrence were noticed. Conclusions We report the first case of an SFT with cystic changes in the lacrimal gland. Although the presence of cavitary lesions alone does not necessarily indicate aggressive behaviour, cystic changes pose a risk of recurrence and may suggest malignant transformation over time. As a result, our case requires long-term follow-up due to recurrence and malignant potential.